Comparing Open and Sealed Bid Auctions: Theory and Evidence from Timber Auctions - Jonathan Levin; Susan Athey; Enrique Seira (Fondazione Eni Enrico Mattei (FEEM), 2004)
We study entry and bidding patterns in sealed bid and open auctions with heterogeneous bidders. Using data from U.S. Forest Service timber auctions, we document a set of systematic effects of auction format: sealed bid auctions attract more small bidders, shift the allocation towards these bidders, and can also generate higher revenue. We propose a model, which extends the theory of private value auctions with heterogeneous bidders to capture participation decisions, that can account for these qualitative effects of auction format. We then calibrate the model using parameters estimated from the data and show that the model can explain the quantitative effects as well. Finally, we use the model to provide an assessment of bidder competitiveness, which has important consequences for auction choice.
Keywords: Q23; D44; 330; Auctions; Timber; Auktionstheorie; Auktion; Holzmarkt; Schätzung; USA